Pembelajaran Berdiferensiasi pada Pembelajaran Matematika: Sebuah Kajian Literatur - Tomo Tomo; Ahmad Yani T; Nurfadilah Siregar; Nadya Febriani Meldi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study discusses the understanding of differentiated learning in mathematics learning and its essence. The research method used is library research. Based on the results of the study, it was found that differentiated learning by paying attention to learning readiness, learning profiles, interests and talents of students is implemented to improve mathematical creative thinking skills. In addition, differentiated learning design as a solution to problems because it accommodates every student's needs and characteristics. In addition, the planned learning already includes differentiation of content, process, product, and learning environment so that efforts that can be made to overcome difficulties in learning mathematics, namely teachers can apply differentiated learning optimally.